THE IMPACT AND APPLICATIONS OF AI LANGUAGE MODELS IN MODERN TECHNOLOGY - Deepak Kumar V; Rajani K; M Shankar Lingam, (International Journal of Advances in Business and Management Research (IJABMR), 2025)
This paper explores the rapidly evolving domain of Artificial Intelligence Language Models (LLMs). It delves into the impact of these models on technology and society, highlighting their applications and potential future developments. The study offers insights into how LLMs are reshaping the landscape of communication, information processing, and AI interactions. At the forefront of modern technological advancements, LLMs such as GPT-4, BERT, and T5 have redefined the boundaries of human-computer interaction through their ability to understand, generate, and engage in human language with remarkable proficiency. Through a comprehensive literature review and analysis of these models, this study sheds light on the historical development, underlying technologies, and current capabilities of LLMs. Employing a mixed-methods approach, the paper synthesizes both quantitative data and qualitative insights to reveal the transformative impact of LLMs across various sectors, including education, healthcare, and business communication. Key findings indicate not only a significant advancement in natural language understanding and generation but also highlight the challenges and ethical considerations inherent in the rapid development of these models. The paper concludes by discussing the potential future trajectory of LLMs, underscoring the necessity for continued innovation balanced with ethical and responsible AI development. This study aims to contribute to the broader understanding of AI LLMs, offering insights into their current applications and charting a course for future research in this dynamic field. The paper concludes by discussing the potential future trajectory of LLMs, underscoring the necessity for continued innovation balanced with ethical and responsible AI development. This study aims to contribute to the broader understanding of AI LLMs, offering insights into their current applications and charting a course for future research in this dynamic field.